Peran pemerintah desa dalam meningkatkan kapasitas UMKM di kelurahan medokan ayu : Peran pemerintah desa dalam meningkatkan kapasitas UMKM di kelurahan medokan ayu - Sri Muljaningsih Mohammad Wahed, mochmmad akbar tri pamudya (Education and Talent Development Center of Indonesia, 2022)
The development of MSMEs in the Medokan Ayu sub-district can have a positive impact on the MSME economy in the Medokan Ayu sub-district. it is necessary to develop relevant businesses so that the existence of MSMEs is able to survive in this competitive modern era MSMEs must provide innovation in their business activities in order to compete with other business actors. However, the development of MSMEs in the Medokan Ayu sub-district, Surabaya is not easy to do because of several obstacles faced, such as product promotion strategies that are not optimal, financial management, and there are still MSMEs that are constrained by NIB even though their business has been running. Keywords: The role of the medokan ayu village in helping the development of medokan ayu SMEs.